ANALISIS PENGARUH KUALITAS PELAYANAN DAN KEPUASAN PELANGGAN TERHADAP LOYALITAS PELANGGAN - Davia Sri Astuti; Mohamad Lutfi (STIE Muhammadiyah Jakarta, 2020)
The business world is getting really competitive these days. Including in providing internet service business. The Supra Primatama Nusantara Inc. or known as Biznet, is one of the services company that runs in the field of providing internet service. Biznet has several products. The product which will be analysed is Biznet Home, a product provided for housing and for apartment that lots of them recently known in need of internet service. Although there are lots of similar competitive products, but Biznet is remain able to stand by doing several strategies. This research itself has the purpose to find out how far is the effect from the Service Quality (X1), the Customer Satisfaction (X2), towards Customer Loyalty (Y), of Biznet Home in Bali. The sample of this research is in amount of 90 respondents by doing the accidental sampling method with the whole population of Biznet Home customers in Bali. The method which is used in this research is quantitative with regression analysis method. There are examination steps such as validation test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple regression analysis, correlation test, determination coefficient test, simultaneously F test, and t statistic test.. This research results that independent variables of service quality (X1) and customer satisfaction (X2) have the significant positive relation towards dependent variable of customer loyalty (Y).